Distributed Generation Placement for Optimal Microgrid Architecture - Vallem, M.R.; Mitra, J.; Patra, S.B. (Proceedings of the ... IEEE Power Engineering Society Transmission and Distribution Conference, 2006)
This paper describes a method for siting of distributed energy resources (DER) within the framework of an optimal microgrid architecture. An optimal microgrid architecture is characterized by minimum cost interconnection, sizing, and siting of DER subject to stipulated global and local reliability criteria. This paper addresses the siting aspect of optimal microgrid architecture. The siting problem considers factors like deployment costs and savings gained by the use of combined heat and power (CHP). The problem is formulated as one of nonlinear programming and simulated annealing optimization is applied. This paper presents the development and implementation of the method, and demonstrates it using a six bus test system